ASSESSMENT OF THE RELATIONSHIP BETWEEN TEMPOROMANDIBULAR JOINT SOUNDS AND BRUXISM - Dimitar Kirov; Lilia Doichinova; Elitsa Deliverska; Janet Kirilova (Peytchinski Publishing, 2022)
Aim of the study: The study aims to assess the possible relationship between bruxism and TMJ sounds. Material and methods: The relationship between temporomandibular joint (TMJ) sounds and bruxism was evaluated in a sample composed of 62 females and 39 males varied in age from 21 to 56 years with a mean age of 40.0±1.07. The participants were informed about the purpose of this study, and they gave their consent. The main methods we used in registering TMJ sound were palpation and auscultation. A self-administered Bruxism Assessment Questionnaire assessed bruxism. Results: The prevalence of bruxism in study group was 60.39% (n = 61) - sleep bruxism (SB) and awake bruxism (AB) were 38.2% and 23.4%, respectively. A total of 53.47% (n = 54) of the sample exhibited some type of clicking joint sound. Chi-square test for independence (with Yates Continuity Correction) indicated significant association between bruxism and TMJ sounds, χ2 (1, n = 101) = 4.183, p = .046, phi = .28. Conclusions: Biomechanical factors seem to play a significant role in TMJ disk displacement development. Based on the research, it should be concluded that bruxism may be associated with joint pathologies, such as disc displacement and joint noises.